Myths in Contemporary Upbringing in a Famaly - Medne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Family discourse has been topical in all periods of anthropogenesis; also nowadays it hasn’t lost its topicality because family is declared as one of the principal values also in this period. Family structure (number of parents and children) is emphasised mainly in contemporary public discourse about a family. Concurrently it is discussed unconnectedly in the public discourse on different kinds of children behavioural difficulties. In this discourse, an important family function – upbringing is disregarded. Aim of upbringing is improvement of attitudes by cooperation of all participants of upbringing in the upbringing environment. Children perspective idea is the leading one in the postmodernism leading pedagogical paradigm that has become the ruling one in the theory and practice. Irrespective of the declared humane principal approaches and principal values myths manifest in the public discourses and in the upbringing area in a family that are made legitimate. Myths develop actively in places where there is lack of information and knowledge and where it is necessary to maintain a sense of safety and emotional balance. So innovative processes of contemporary society activate also the issues on place of myths on the upbringing process.Aim of the article is to analyse theoretically the subjective and objective provisions for creation of myths, their importance in the upbringing process in a family, outlining the risks in upbringing.